Design and characterization of strain hardening curauá fiber cement-based composites - Żukowski, Bartosz (2017)
This work presents the application of the theoretical model to design the strain hardening cement-based composite reinforcement with natural curauá fiber. The work investigates the properties of curauá fiber and the influence of hot water washing cycles and alkaline treatments on fiber strength. The fiber-matrix bond is investigated by pullout tests. The collected data is implemented into the theoretical model for minimum fiber volume needed to achieve strain hardening behavior. The influence of fiber length on mechanical performance of the composite is investigated. In the final stage, the composites were exposed to natural weathering, wetting and drying cycles, and freeze and thaw cycles to verify the durability of the strain hardening behavior as well as the curauá fiber in the cement-based matrix.